Forgery, replica, fiction : temporalities of German Renaissance Art - Wood, Christopher S. (Univ. of Chicago Press, 2008)
Credulity -- Reference by artifact -- Germany and "Renaissance" -- Forgery -- Replica -- Fiction -- Re-enactment